Vessel risks to marine wildlife in the Tallurutiup Imanga National Marine Conservation Area and the eastern entrance to the Northwest Passage. Issue 127 (January 2022) - Halliday, William D.; Dawson, Jackie; Yurkowski, David J.; Doniol-Valcroze, Thomas; Ferguson, Steven H.; Gjerdrum, Carina; Hussey, Nigel E.; Kochanowicz, Zuzanna; Mallory, Mark L.; Marcoux, Marianne; Watt, Cortney A.; Wong, Sarah N.P.
Abstract: The Arctic is changing rapidly due to climate change, which is allowing unprecedented levels of vessel traffic to transit the region. Vessel traffic can negatively affect marine wildlife in a number of ways, particularly in areas where vessels overlap with high concentrations of ecologically important species, and the significance of these impacts are of increased concern when the wildlife are also culturally important. Tallurutiup Imanga National Marine Conservation Area, located in Lancaster Sound, Nunavut, Canada, at the eastern entrance to the Northwest Passage, is experiencing the greatest levels of vessel traffic in the Canadian Arctic, and is important habitat for marine wildlife, including marine mammals and seabirds. Here, we examined the overlap between vessel traffic, including modeled underwater noise levels, and the distribution of two cetacean species, beluga and narwhal, and three seabird species, thick-billed murre, northern fulmar, and black-legged kittiwake. Narwhal had the highest vessel risk in Eclipse Sound and Milne Inlet, all three seabirds had high vessel risk at the eastern entrance to Eclipse Sound, with additional areas for northern fulmar at southern Devon Island and for black-legged kittiwake at Prince Leopold Island, and belugas had the highest vessel risk along southern and eastern Devon Island. Our results provide crucial information for implementing monitoring, conservation, and management initiatives for species inhabiting this protected area, and allow for a better understanding of the potential cultural implications of vessel-based marine wildlife impacts that will affect traditional subsistence hunting and local livelihoods. Highlights: Vessel traffic is increasing in the Arctic, and with it, risk to marine wildlife. We examined risk from vessels to marine wildlife in Tallurutiup Imanga, Nunavut. Narwhal and seabirds had highest vessel risk in Eclipse Sound and Milne Inlet. Belugas had highest vessel risk along southern and eastern Devon Island. Continued monitoring is needed to track risk to wildlife as vessel traffic increases.